Factor product utilization and health outcomes in patients with haemophilia A and B on extended half‐life concentrates: A Canadian observational study of real‐world outcomes. Issue 5 (23rd June 2021) - Sun, Haowei (Linda); Yang, Ming; Poon, Man‐Chiu; Lee, Adrienne; Robinson, K. Sue; Sholzberg, Michelle; Wu, John; Iorio, Alfonso; Blanchette, Victor; Carcao, Manuel; Klaassen, Robert J.; Jackson, Shannon
Abstract: Introduction: Recombinant factors VIII and IX Fc (rFVIIIFc/rFIXFc) became available in Canada in 2016 and were the only extended half‐life (EHL) factor concentrates available in Canada until 2018. Objectives: We aim to describe the change in product utilization in Canadians who switched to rFVIIIFc/rFIXFc. Methods: This prospective and retrospective cohort study enrolled males aged ≥6 years with moderate or severe haemophilia who switched to rFVIIIFc/rFIXFc and those who remained on standard half‐life (SHL) between 2016 and 2018. Factor utilization and annualized bleeding rates (ABR) were collected at baseline, 1‐year and 2‐years. Due to low prospective enrolment (n = 25 switchers), prospective and retrospective data were pooled. Results: 125 switchers (93 rFVIIIFc, 32 rFIXFc) and 33 non‐switchers were included. The median age was 17 (rFVIIIFc) and 38 years (rFIXFc). Prior to switch, over 80% were on prophylaxis. There was a statistically significant reduction in the prescribed weekly prophylactic dose after the switch to rFVIIIFc/rFIXFc for all age groups, with a corresponding reduction (15‐16%) in actual annualized FIX utilization in switchers (combined adults and children) to rFIXFc, and a smaller non‐significant reduction in actual annualized FVIIII utilization (7%) in children who switched to rFVIIIFc. A significant reduction in the median ABR was only observed in children who switched to rFVIIIFc, but not in adults who switched to rFVIIIFc or rFIXFc. Conclusion: Switching from SHL to EHL products led to a small reduction in factor utilization, while preserving a low ABR in children and adults with haemophilia. Further patient‐reported outcomes data will further elucidate the role of EHL in the haemophilia landscape.